Project Activities Strengthening the Profile of Pancasila Students with Learning Based on Local Cultural Wisdom - Utami, Budi; Probosari, Riezky Maya; Indriyanti, Nurma Yunita; Fakhrudin, Isma Aziz; Khasanah, Annisa Nur; Supurwoko, Supurwoko; Wardani, Putri Kusuma (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
This research aims to determine the implementation of project activities to strengthen the Pancasila Student Profile at State Junior High School 1 (SMP Negeri 1) Surakarta, Central Java, Indonesia, and the impact of its implementation on students. The profile of Pancasila students is: 1) Believer, devoted to God Almighty and has noble character, 2) Independent, 3) cooperation, 4) Global diversity, 5) Critical reasoning, 6) Creative based on local wisdom by making Batik, namely Batik Jumputan and Written Batik, in Solo (Surakarta), Central Java, Indonesia. The research population was in one of the junior high schools in Surakarta (SMP Negeri 1 Surakarta). The Pancasila Student Profile can be identified as starting to develop, currently developing according to expectations, and very developing. From the observations, it is known that the Project for Strengthening the Profile of Pancasila Students (P5) at SMP Negeri 1 Surakarta has developed according to expectations by 60% and has developed very well at 40%. However, there is still a weakness, namely that the assessment of the aspects of the Project for Strengthening the Profile of Pancasila Students (P5) as a group is not yet known individually so the aspects that stand out individually are not yet known.